The Influence of Accounting Information System Cash Sales and Internal Control of Sales Effectiveness - Herlina Kustianti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This purpose of this research is to: (1) determine the magnitude of the effect of the cash sales accounting information system on sales effectiveness. (2)determine the magnitude of the effect of internal control on sales effectiveness.The research subject was AUTO2000 Marketing Department of Toyota, the Soekarno Hatta Bandung branch and the object of research was accounting information systems and internal control and sales effectiveness. Data collection techniques used by distributing questionnaires to 35 respondents of Toyota AUTO2000 branch of Soekarno Hatta Bandung. The data obtained were then analyzed using validity test, descriptive method descriptive method, and verification method. The results of statistical testing in the accounting information system has a significant positive effect on sales effectiveness, internal control has a significant effect on sales effectiveness.